2018
DOI: 10.1097/md.0000000000011828
|View full text |Cite
|
Sign up to set email alerts
|

Improving nontechnical skills of an interprofessional emergency medical team through a one day crisis resource management training

Abstract: Errors are frequent in healthcare, but Emergency Departments are among the highest risk areas due to frequent changes in team composition, complexity and variety of cases, and difficulties encountered in managing multiple patients simultaneously.Crisis resource management (CRM) training has been associated with decreased error rates in the aviation industry as well as in certain areas of acute medical care, such as anesthesia and emergency medicine. In this study, we assessed whether a single day CRM training,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…Yee et al [24] also evaluated one similar CRM intervention and showed improvement at 1 and 2 months in all NTS categories. However, other studies do not show this retention [23]. CRM training is incorporated into a wider urology curriculum by Khan et al [21], which shows feasibility and acceptability.…”
Section: Crisis Resource Management and Ward-based Scenariosmentioning
confidence: 98%
See 4 more Smart Citations
“…Yee et al [24] also evaluated one similar CRM intervention and showed improvement at 1 and 2 months in all NTS categories. However, other studies do not show this retention [23]. CRM training is incorporated into a wider urology curriculum by Khan et al [21], which shows feasibility and acceptability.…”
Section: Crisis Resource Management and Ward-based Scenariosmentioning
confidence: 98%
“…CRM training, which addresses NTS in emergency scenarios, has been used successfully in aviation and acute care and is associated with a reduction in errors. Truta et al [23] created a single-day CRM course with both didactic and simulation training for interprofessional EM teams. It resulted in significant NTS improvement two months following the course in all aspects of NTS for all levels of training.…”
Section: Crisis Resource Management and Ward-based Scenariosmentioning
confidence: 99%
See 3 more Smart Citations